Impacts of groundwater contamination with fluoride and arsenic: affliction severity, medical cost and wage loss in some villages of India - Indu, Rajnarayan; Krishnan, Sunderrajan; Shah, Tushaar (2007)
In India, high fluoride concentration in groundwater (greater than 1 mg/l) is widespread in the arid to semi-arid western states of Rajasthan and Gujarat and in the southern states of Andhra Pradesh, Karnataka and Tamil Nadu. A field research study conducted at six areas severely affected by fluorosis shows that affordability of safer drinking water is related to higher income level, and that the severity of fluorosis affliction is higher for lower income levels. The cost incurred on medicines and loss of wages is a significant proportion of the earnings and has a general debilitating impact on the affected families. As compared with fluorosis, the skin afflictions of arsenicosis carry greater social stigma and patients incur higher costs. In Nadia district of West Bengal, the impacts of arsenic contamination are more severe with increasing age. Cumulatively, over the entire afflicted population, both fluoride and arsenic contamination have a high cost on society and addressing the problem would require more attention from government agencies and society apart from individual awareness.